Branding tourism and collaborative governance: A case study from Nglanggeran village - Mohamad Sukarno; Dyah Mutiarin (Faculty of Communications Science, Dr. Soetomo University, 2023)
Nglanggeran Village has been recognised as a smart tourism destination and earned the